Effect of Asset Structure, Profitability, and Financial Leverage on Capital Structure in Companies Registered on the Jakarta Islamic Index 70 (JII70) for the 2019-2021 Period - Ramadhan, Gion; Sari, Tati Emi Puspita; Harahap, Nur Anisyah; Nanda, Irvan; Dewi, Citra (ADPEBI, 2022)
Infrastructure companies need very serious attention to company assets that will be related to decision making. The decision-making in question is a funding decision. The purpose of this study was to determine the effect of asset structure, profitability, leverage, and financial leverage on capital structure of infrastructure companies. This study uses the Panel Data analysis method. The panel data regression consists of observations in the same cross section or individual and for several time periods (time series). The results of data analysis carried out using Spss 20 get the results of the t-test that the asset structure, profitability, leverage and financial have a significant effect on the capital structure of infrastructure companies. The contribution given by the independent variable to the dependent is 14,6%.